Valuation of the option of early reversion in road concessions - Antonio Sánchez Soliño; Antonio L. Lara Galera; Fernando Cabero Colín (European Journal of Transport and Infrastructure Research, 2018)
In recent years there has been an increase in the interest in contractual flexibility in infrastructure investments, especially in Public-Private Partnership agreements, characterized by the uncertainty derived from the long duration of contracts. This has led to the extension of the theory of real options to the field of infrastructures, as an appropriate methodology for analyzing flexibility in contracts. Within this line of research, this paper focuses on the analysis of the option of early reversion of road concessions, as a right held by the Public Administration and whose value depends on the evolution of a random variable, the volume of traffic. The real option approach is applied to the case study of a road concession in Spain, consequently obtaining significant values for the probability of exercising the option. More generally, this paper contributes to characterizing the early reversion option as a practical tool that can be used by the Administration for the implementation of the infrastructure policy.